L'abus des fonctions dans la relation préposé-commettant en droit civil québécois. - Masse, Claude (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
The following article deals with the problem of « misuse of office » in the principal-agent relationship under Quebec civil law. Despite the abundance of case law, solutions to the problem are not well defined especially in cases involving personality defects of the agent. The law concerning « misuse of office » is generally to be found in article 1054(7) of the Quebec Civil Code concerning the liability of principals. This controverted article not only deals with the liability of masters for servants, but also with the problem of torts committed by agents (art. 1731 C.C.). It also has an effect on workmen's compensation laws. The main issue in « misuse of office » is the determination of what constitutes a carrying out of duties within the scope of employment. The principal can only be held liable for the tort of an agent if three conditions are met : the tort feasor must have been his agent ; he must have committed a wrongful act ; and this act must have been committed in the scope of his employment. After a general view of the fundamental principles involved, the paper defines « misuse of office » as « all torts committed by an agent in the exercice of his duties, even when not authorized to carry out the duties in the manner which he did, but where the activity is designed to benefit his principal ». The only case where the principal escapes liability is where the agent committed a tort which did not involve his work. The agent in that case no longer acts for the benefit of his principal, but is pursuing his personal interest. The principal is then no longer held liable. Determination of the notion of « benefit » therefore becomes essential. Far from being a simple question of monetary profit, it is extended to mean any activity which can serve the principal's enterprise, whether in the improvement of public relations, or of relations with staff or suppliers. The pecuniary gain becomes but one element amongst many others. It is not even necessary for the benefit to ever materialize. The simple fact that the intention was to benefit the principal is sufficient. The review of the case law leads the author to conclude that the modification of the ways in which the duties are carried out has little effect on the liability of the principal. For instance, the agent can change the time, the place and the manner of performance and still engage the liability of the principal. Quebec courts have gone even further. They have held that an agent can go beyond the usual scope of his duties or take up some that he was not authorized to do, without affecting the liability of the principal. In fact, Quebec courts have developed a broad interpretation of the notion of duty. They consider that the agent is called upon to perform tasks more or less accessory to his main duties and thus extend the principal's liability to all of them. As already stated, the notion of «benefit to the principal» is a determining factor. It is not necessary that the agent's work for the principal be exclusive. The agent that derives a personal benefit and simultaneously intends to benefit the principal, will still be considered to have performed an act in the course of his duties. The paper examines a series of problems involving the personality of the agent. Certain tortious acts can be committed in relations with third parties or co-workers, and are the direct result of a personality defect of the agent. Such is the case of a restaurant worker who physically attacks a client as the result of a dispute or of the agent stealing from a client. The paper points out the great difficulty that Quebec courts have experienced in the legal qualification of this situation. After an in-depth study of the Quebec case law, the paper concludes that the trend is to maintain the liability of the principal in these cases. One criterion appears to be well defined : the principal bears the responsibility, when hiring someone, to assure his clients or the persons with whom he does business, that he will respect their property as well as their moral and physical integrity. The necessary tie between the duties of the agent and the relationship with persons coming in contact with him, will engage the liability of the principal. Every time the agent comes in contact with a person in the carrying out of business, the principal will be held responsible for the damage resulting from personality defects of the agent. In all other cases, the relation will be considered personal to the agent and the principal will be relieved of any liability.